2017
DOI: 10.1111/ajt.14103
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Targeting Myofibroblast Contractility and Extracellular Matrix Cross-Linking as a Therapeutic Concept in Airway Fibrosis

Abstract: Fibrosis after solid organ transplantation is considered an irreversible process and remains the major cause of graft dysfunction and death with limited therapies. This remodeling is characterized by aberrant accumulation of contractile myofibroblasts that deposit excessive extracellular matrix (ECM) and increase tissue stiffness. However, studies demonstrate that a stiff ECM, itself, promotes fibroblast-to-myofibroblast differentiation, stimulating further ECM production. This creates a positive feedback loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…Myofibroblasts are known to contribute to the contractile behaviour of the airways via their expression of molecules that directly interact with and impact on the ECM and the cytoskeletal network 53 . We found that focal adhesion molecule ITGB1 was upregulated in myofibroblasts as expected 5456 .…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblasts are known to contribute to the contractile behaviour of the airways via their expression of molecules that directly interact with and impact on the ECM and the cytoskeletal network 53 . We found that focal adhesion molecule ITGB1 was upregulated in myofibroblasts as expected 5456 .…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs developed for treatment of pulmonary fibrosis may be potential candidates for the treatment of intestinal fibrosis. Pirfenidone (a growth factor inhibitor), SD‐208 (a TGF‐βR1 signaling blocker), Nintedanib (a kinase inhibitor that acts on vascular endothelial fibroblast growth factor receptors), Integrin αvβ6 (activates latent TGFβ) inhibitor, Simtuzumab (a monoclonal antibody to LOXL2) in combination with Relaxin (an inhibitor of myofibroblast contraction), rapamycin and its analogs, sirolimus and everolimus (through their immunosuppressive and anti‐fibrotic action), serotonin (inducer of myofibroblast activation) receptor inhibitors, and Rho kinase (activator of mesenchymal cells) inhibitor have shown some success in the treatment of pulmonary fibrosis in humans and in experimental intestinal fibrosis in animal models. The real clinical effectiveness of these agents in IBD remains to be defined in human trials.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 99%
“…Therefore, disruption of the α-SMA by siRNA knockdown affects the contraction of myofibroblasts, thus reducing the assembly of fibronectin matrix into fibrillary ECM. In addition, a recent study in airway fibrosis has also found that by simultaneously utilizing relaxin and LOX inhibitors to target myofibroblastic contractility and matrix stiffness, respectively, showed that the deposition of collagen could be significantly reduced and the re-epithelialization of remodeled airways could be promoted 98.…”
Section: Targeting the Matrix Mechanics In Liver Fibrosismentioning
confidence: 99%